Synthesis and Antimicrobial Activity of Some Novel Chalcones of 2-Hydroxy -1-Acetonapthone and 3-Acetyl Coumarin - Y. Rajendra Prasad; P. Ravi Kumar; Ch. Asha Deepti; M. Venkata Ramana (E-Journal of Chemistry)
Five novel chalcones were synthesised by condensing 2-hydroxy-1-acetonaphthone with aldehyde derivatives in dilute ethanolic potassium hydroxide solution at room temperature according to Claisen-Schmidt condensation and another five novel chalcones were prepared by refluxing 3-acetyl coumarin with aldehydes in the presence of piperidine in ethanol. All these compounds were characterised by means of their IR, 1H NMR spectroscopic data and microanalyses. The antimicrobial activity of these compounds were evaluated by the cup plate method.